2021
DOI: 10.1186/s13073-020-00808-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of epigenome-wide DNA methylation differences between carriers of APOE ε4 and APOE ε2 alleles

Abstract: Background The apolipoprotein E (APOE) ε4 allele is the strongest genetic risk factor for late onset Alzheimer’s disease, whilst the ε2 allele confers protection. Previous studies report differential DNA methylation of APOE between ε4 and ε2 carriers, but associations with epigenome-wide methylation have not previously been characterised. Methods Using the EPIC array, we investigated epigenome-wide differences in whole blood DNA methylation pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 75 publications
2
41
0
Order By: Relevance
“…This result indicates combining multiple omics data can yield better insights into the underlying mechanisms of diseases. It can also be observed that the classification performance using DNA methylation profile alone and miRNA expression profile alone was almost identical and the performance of the two different multi-omics combinations (i.e., gene expression+DNA mehyltaion and gene expression+DNA methylation+miRNA expression) was not significantly different, which indicated that miRNA expression profiles and DNA methylation profiles providing overlapping information for the tumour type classification task [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates combining multiple omics data can yield better insights into the underlying mechanisms of diseases. It can also be observed that the classification performance using DNA methylation profile alone and miRNA expression profile alone was almost identical and the performance of the two different multi-omics combinations (i.e., gene expression+DNA mehyltaion and gene expression+DNA methylation+miRNA expression) was not significantly different, which indicated that miRNA expression profiles and DNA methylation profiles providing overlapping information for the tumour type classification task [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Human data on postbiotics and DM are lacking, and we identified only one trial on this topic in healthy adults [ 85 ]. It is likely that ethnic group [ 138 , 139 ], sex [ 140 ], and the time course of DM [ 141 ] influence the GM response to postbiotic treatments, and these aspects should be contemplated in human studies. Many of the included studies did not analyse the changes in the GM following the interventions, and this would provide valuable information about the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that childhood obesity increases the risk for adult T2D and coronary artery disease (CAD) [ 29 , 30 ]. Information on childhood BMI was not available for UKB participants but a related childhood measure of a comparative body size at age ten was available for 287,203 participants, among them 156,307 (54.42%) were females.…”
Section: Resultsmentioning
confidence: 99%